2018
DOI: 10.1002/hep4.1167
|View full text |Cite
|
Sign up to set email alerts
|

The molecular adsorbent recirculating system in posthepatectomy liver failure: Results from a prospective phase I study

Abstract: Posthepatectomy liver failure (PHLF) represents the single most important cause of postoperative mortality after major liver resection, yet no effective treatment option is available. Extracorporeal liver support devices might be helpful, but systematic studies are lacking. Accordingly, we aimed to assess the safety and feasibility of the Molecular Adsorbent Recirculating System (MARS) in patients with PHLF. Between December 2012 and May 2015, a total of 206 patients underwent major or extended hepatectomy, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 40 publications
0
12
0
2
Order By: Relevance
“…Recent reports focused on validating especially the ISGLS criteria [9,19] but on the other hand, even the '50:50' criteria as well as the Mullen criteria are still used in current publications [20,21]. In a recently published Swedish single-center study on extracorporeal liver support in patients with PHLF, the 50:50 criteria were found to serve as valid inclusion criteria [22]. Therefore, the 50:50 criteria have been used to define PHLF in the current study, too.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports focused on validating especially the ISGLS criteria [9,19] but on the other hand, even the '50:50' criteria as well as the Mullen criteria are still used in current publications [20,21]. In a recently published Swedish single-center study on extracorporeal liver support in patients with PHLF, the 50:50 criteria were found to serve as valid inclusion criteria [22]. Therefore, the 50:50 criteria have been used to define PHLF in the current study, too.…”
Section: Discussionmentioning
confidence: 99%
“…To compensate for the loss of liver function, extracorporeal hepatic support devices have been evaluated in patients presenting with acute post-operative liver failure. These devices, such as MARS®, Prometheus®, and SPAD, are albumin-linked hemodialysis systems that improve the biochemical parameters of patients but fail to improve survival rates[ 33 ]. A study combining the use of both liver support and portal ring devices needs to be envisaged in the future so as to determine the effects on perioperative outcomes and long-term survival.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, therapy with the molecular adsorbent recirculating system was shown to attenuate hyperbilirubinemia and hepatic encephalopathy in patients with postoperative LD, even though its impact on survival was limited in more recent analyses (19,20). However, growing evidence suggests that liver support devices are primarily effective, if they are introduced early, which further underlines the importance of a tool for early risk assessment, such as the 3-60 criteria (21,22). Here, the 3-60 criteria might lead to augmented results, as early introduction of the molecular absorbent and recirculation system might be used as a bridging therapy for patients classified as high risk no later than POD1, which in turns could lead to further improvement of patients' outcome.…”
Section: Discussionmentioning
confidence: 99%